relacion entre el nivel de ataque y daños de Pectinophora goáypiella (Saunders) en algodon - Alvarado, A.=700 1 Carrasco, I.; Castillo, M.A.; Duran, J.M.; De la Rosa, A.
(Es, En)
ilus., 4 ref.
Keywords: PECTINOPHORA GOáYPIELLA; ALGODON; DAÑOS; PERDIDAS; ESPAÑA